'I'm still not sure what a task is': Teachers designing language tasks. (May 2016) - Erlam, Rosemary
Ellis (2003) identifies four key criteria that distinguish a 'task' from the types of situational grammar exercises that are typically found in the more traditional language classroom. This study investigates how well teachers were able to design tasks that fulfilled these four criteria (Ellis, 2003) at the end of a year-long professional development programme in which TBLT figured prominently. Forty-three tasks designed by the teachers for use in their own foreign language classrooms are analysed against Ellis's four criteria in order to evaluate the effectiveness of the professional development programme, on the premise that adequate understanding of the construct of task underpins successful implementation of TBLT. The findings show that some aspects of task-design were difficult for teachers. Implications for professional development programmes that focus on TBLT, such as the one whose effectiveness is evaluated here, are discussed.